PENGARUH SENAM AEROBIK INTENSITAS RINGAN DAN SEDANG TERHADAP KADAR LDL PADA PEREMPUAN OBES DI KOTA BATU - Agung Budi Suhardiansyah; Rias Gesang Kinanti; Slamet Raharjo (Universitas Negeri Malang, 2016)
Abstract: the purpose of this research is to reveal the influence of low and medium intensityaerobics towards the level of obese women’s ldl, using matching pretest-posttes comparison group design dengan 2 kelompok yaitu kelompok senam aerobik intensitas ringandan kelompok senam aerobik intensitas sedang. Sampel penelitian yang digunakan adalah perempuan obes yang memiliki imt >25,0 sebanyak 20 orang. Penelitian dilakukan selama 8 minggu.pengumpulan data dilakukan dengan memeriksa kadar trigliserida darah menggunakan alat spectrophometer. While the analysis of the data in this study using t-test which includes two paired samples and two independent samples with 0.05 significances level. The result of two paired sample t-test, sig < α in which the low intensity is 0 <0.05 and medium intensity 0.001 < 0.05. This shows there is the influence of light intensity aerobic exercise and moderate intensity. The results of two-sample t-test free sig 0.003 <0.05 mean ldl levels by moderate intensity aerobic exercise and light intensity aerobics (18.2430> 3.5942), so it can be concluded that there is a difference between the effects of light intensity aerobic exercise of moderate intensity on ldl levels.Key words: aerobic gymnastic, ldl, obesity